P0451TEN-YEAR OUTCOME DIFFERENCES IN LUPUS NEPHRITIS PATIENTS TREATED WITH CYCLOPHOSHAMIDE AND MYCOPHENOLATE- BASED TREATMENT REGIMEN. (6th June 2020) - Prasad, Narayan; Kurian, Jithu; Agarwal, Vikas; Bhadauria, Dharmendra; Gupta, Amit
Abstract: Background and Aims: Lupus nephritis (LN) poses a considerable impact on the morbidity and mortality of SLE patients. Long term comparative outcome data with cyclophosphamide (CYP) and mycophenolate mofetil (MMF) based regimen from the Indian subcontinent is sparse. We assessed the renal and patient survival of these patients for the types of induction CYP or MMF and the two maintenance therapies – MMF or Azathioprine. We determined the predictors of death and dialysis dependency in the study population. Method: In this retrospective study, we analysed outcomes of 100 LN patients, total 67 (26 class III, 25 class IV, 6 class III+V, and 10 class IV+V)) treated with CYP (euro lupus-40 and NIH- Dharmendra Bhadauria 27), and 33 with MMF based regimen with the steroid between July 2008 to June 2018. The class distribution of the patients in the two groups was similar. The data were archived regarding demography, clinical, histopathological features, and the treatment given of all 100 biopsy-proven LN patients. Outcomes between two regimens CYP and MMF in terms of remission, dialysis dependency, and patient survival were compared. The renal survival and patient survival at the end of follow-up between two groups were also analysed. Results: The clinical characteristics were similar in both groups, except the activity index was high in CYP patients (6.13 ±4.48 Vs. 4.61 ± 2.80); however, the chronicity index was similar. The overall remission was 70% at the end of induction. The CR, PR, and NR in the CYP group was 46.2%, 23.9 %, 29.9% respectively; however, in the MMF group was 57.6%, 12.1%, and 30.3%, respectively. More patients died in CYP (14.9%) than those in MMF (9.1 %) patients. The 1-, 2-, 3-, 4-, 5- and 10-years patient survival in the CYP induction was 89.5%, 86.2%, 86.2%, 83.8%, 83.8% and 83.8% however in MMF was 93.9%, 93.9%, 89%, 89%, 89% and 89% respectively. The most common cause of death was sepsis 9/13(69.2%), followed by uremia. The high serum creatinine, low Hb, male, thrombocytopenia, microscopic haematuria, leukocyturia, nephrotic proteinuria, lack of remission in 12 months, dialysis, doubling of creatinine on follow-up were significant predictors of mortality. The 1-, 2- 3-, 4-, 5- and 10- years renal survival (event death-censored, but dialysis dependency) in CP group was 98.5%, 96.7%, 94.7%, 92.4%, 92.4% and 84 % respectively however in the MMF was 96.8 %, 96.8%, 91.9%, 91.9%, 91.9%, and 78.8% respectively. (Figure 1)At the end of the study, dialysis dependency in the MMF group and CYP group was 7.5% and 12.1 %, respectively (NS). In the maintenance therapy, 3/56(5.3%) had to double of creatinine in MMF, and 7/34 (20.5%) in the AZA group (p=0.03). Conclusion: Long term outcomes in terms of patient and renal survival of LN patients treated with CP and MMF based induction is similar. Serum creatinine doubling was more with MMF than AZA based maintenance. The majority of death occurred during induction, and sepsis was the most common cause of death.